The influence of body condition and personality on nest defense behavior of Japanese tits (Parus minor) - Mingju E; Chao Shen; Nehafta Bibi; Yu Zhang; Li Liu; Xudong Li (Animal Cognition)
Abstract When faced with a predator, parent birds have to choose between current and future breeding. Previous studies have shown that the body condition and personality of parents influence the trade-offs. However, whether body condition and personality influence an individual’s nest defense behavior has rarely been investigated. Here, we studied whether body condition and personality affect the nest defense behavior of incubating Japanese tits (Parus minor). Some females exhibited intense nest defense behavior when human-simulated intruders approached. Notably, individuals exhibiting high nest defense behavior had significantly shorter tail lengths compared to individuals who did not. In addition, bold individuals would exhibit higher nest defense behavior than those showing low defense responses. Furthermore, bold individuals consistently demonstrated stronger nest defense behavior compared to shy individuals, aligning with their proactive personality traits. This pattern highlights the potential role of individual behavioral differences in shaping anti-predator strategies.